2005
DOI: 10.2131/jts.30.s163
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Two-Generation Reproduction Toxicity Study Adding Endopoints to Detect Endocrine Disrupting Activity Using Vinclozolin

Abstract: -A two-generation reproduction toxicity study in rats adding extra endpoints to detect endocrine disrupting activity was conducted using vinclozolin by dietary administration at 0, 40, 200, and 1000 ppm, for investigation of its utility. The extra endpoints included anogenital distance (AGD), nipple development, sexual maturation (vaginal opening and preputial separation), estrous cycle, spermatogenesis, sex organ weights, and blood hormone concentrations (thyroid and sex hormones). Hepatic drugmetabolizing en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…In adult female rats, vinclozolin induced alterations in the serum profiles of LH and the E 2 :testosterone ratio, which could collectively account for the prolongation of estrous cycle duration that was measured in these animals [133]. In a two-generation reproductive toxicity study, 40-1000 ppm dietary vinclozolin resulted in hyperplasia of ovarian interstitial cells and vacuolation of lutein cells in females of both generations [134].…”
Section: -Effects Of Estrogenic and Anti-androgenic Endocrine Disrupmentioning
confidence: 95%
See 1 more Smart Citation
“…In adult female rats, vinclozolin induced alterations in the serum profiles of LH and the E 2 :testosterone ratio, which could collectively account for the prolongation of estrous cycle duration that was measured in these animals [133]. In a two-generation reproductive toxicity study, 40-1000 ppm dietary vinclozolin resulted in hyperplasia of ovarian interstitial cells and vacuolation of lutein cells in females of both generations [134].…”
Section: -Effects Of Estrogenic and Anti-androgenic Endocrine Disrupmentioning
confidence: 95%
“…In adult female rats, vinclozolin induced alterations in the serum profiles of LH and the E 2 :testosterone ratio, which could collectively account for the prolongation of estrous cycle duration that was measured in these animals [133]. In a two-generation reproductive toxicity study, 40-1000 ppm dietary vinclozolin resulted in hyperplasia of ovarian interstitial cells and vacuolation of lutein cells in females of both generations [134].In studies using pregnant rats that were given oral vinclozolin (3.0-10μg/ml), it has been shown that this compound antagonizes the androgenic effects of testosterone propionate in male and female embryos [135]. Further analysis of the in utero effects of vinclozolin revealed that male embryos underwent feminization and female embryos became masculinized when dams were given vinclozolin.…”
mentioning
confidence: 96%
“…In two earlier two-generation studies, reduced fertility in the P0 and P1 generations was observed through reduced live birth indices (Hellwig, 1992;. Moreover, Matsuura et al (2005) found histopathological effects on adrenals, pituitary, testis, seminal vesicles, and ovaries in P0 and P1. In addition, T4 was dose-dependently decreased, anogenital distance was reduced, and preputial separation was delayed in F1 males.…”
Section: Rorije Et Al "Impact Of 2nd Generation Mating and Offspringmentioning
confidence: 85%
“…Accepted for publication in "Regulatory Toxicology and Pharmacology dd.18-8-2011 Matsuura et al (2005) reported a reduced fertility in the P1 but not in the P0 males. In two earlier two-generation studies, reduced fertility in the P0 and P1 generations was observed through reduced live birth indices (Hellwig, 1992;.…”
Section: Rorije Et Al "Impact Of 2nd Generation Mating and Offspringmentioning
confidence: 99%
“…persistent changes occurred in the gene expression [242]. In the case of VCZ two-generation studies reveal that when given in the diet to pregnant rats changes occur in the ano-genital distance, sex organ weights, sexual maturation and blood hormones in both F1 and F2 male offspring [244,245]. The effects of VCZ are permanent and are most pronounced when administered transiently during the period of gonadal sex differentiation [246,247].…”
Section: Transgenerational Effectsmentioning
confidence: 99%